Microtrabecular Fracture with Intramedullary Fat Globules - Jeroen Bauwens; Koenraad Nieboer (Journal of the Belgian Society of Radiology, 2023)
Teaching Point: In rare cases, trauma may result in intramedullary fat globules which have a characteristic aspect both on MRI and dual-energy CT.